Nourishment, health, work and socio-economic status of six sugar cane agricultural worker families, in Barreiros Pernambuco, Brazil (Nutrição, saúde, trabalho e status socioeconômico de seis famílias de agricultores em Barreiros, Pernambuco, Brasil) - Amaral, Ana Elizabeth Perruci do (Ciência & Trópico, 2011)
RESUMO Aborda alguns aspectos relacionados com a subnutrição no Brasil. São focados os padrões de saúde e alimentação, as condições de trabalho e o status socioeconômico dos agri¬cultores da cana-de-açúcar. Resultado de estudo baseado em entrevistas com o chefe da família, a esposa e membros de seis famílias, e observações feitas nas residências rurais. São unidades de análise as famílias de trabalhadores “permanentes" – aqueles com contratos de trabalho permanente e salário regular. Eles têm características homogêneas. A escolha dos entrevistados foi aleatória na “Zona da Mata Sul de Pernambuco”, Barreiros, em maio de 1985. A eficiência dos trabalhadores agrícolas tem sido prejudicada em virtude da saúde e alimentação deficientes. Estas são conseqüências de sua baixa renda e a alta da inflação. Este estudo trouxe à tona novas idéias acerca da relação entre alimentação, saúde e trabalho na agricultura da cana-de-açúcar. Permitiu também o desenvolvimento de uma metodologia para uma pesquisa mais ampla, no futuro, e a geração de material descritivo para análise e apresentação de estudo de caso. Sugestões são dadas, como a mudança de hábitos ali¬mentares, o suprimento de alimentos no local de trabalho e a distribuição de terra acompanhada de orientação técnica quanto à sua utilização, dos instrumentos de crédito e implementos agrícolas. ABSTRACT Nourishment, health, work and socio-economic status of six sugar cane agricultural worker families, in Barreiros Pernambuco, Brazil. v. 16, n. 2, p. 159-170, jul./dez. 1988. This paper explores some factors related to malnutrition in Brazil. Attempts are made to focus on health and nourishment patterns, work conditions and socio-economic status of sugar cane agricultural workers. It is a result of an exploratory study carried out through semi-structured interviews-with the head, wife and members of six families and observations made in the rural homes. Its units of analysis are families of “permanente” workers - those with permanent work contracts and regular income. They have homogeneous characteristics. The choice of the interviewed was made at random in the “Zona da Mata Sul” of Pernambuco, district of Barreiros, in May, 1985. The main findings are: the efficiency of these agricultural workers have been harmed because of their deficient health and nourishment. These are consequences of their low income and high inflation. This study brought to the surface, new ideas about the relationship among nourishment, health and work in sugar cane agriculture. It allowed also, the development of a methodology for broader research, in the future, and the generation of initial descriptive material for analysis and presentation of a study case. In this paper, are also given some suggestions about the studied problem, like the change of nourishment habits, the supply of food in the work place and the distribution together with technical orientation regarding their utilization, credit instruments and agricultural implements. RÉSUMÉ Nutrition, santé, travail et status socioéconomique de six familles d’agriculteurs à Barreiros, Pernambuco, Brasil. v. 16, n. 2, p. 159-170, jul/dez. 1988. Cet article traite des aspects liés à la sous-nutrition au Brésil, le niveau de santé et d’alimentation, les conditions de travail et le status socioéconomique des agriculteurs de la canne à sucre. C’est le résultat d’une étude basée en quelques interviews avec des chefs de famille, l’épouse et membres de six familles, et des observations faites dans des maisons rurales. Les unités d’analyse sont les familles des travailleurs “permanents” – ceux qui ont des contracts de travail permanent et salaire régulier. Ils ont des caractéristiques homogènes. Le choix des interviews a été aléatoire dans la Zone da Mata Sud de Pernambuco, Barreiros, en Mai, 1985. L’efficacité des travailleurs agricoles diminue en raison de la santé et de l’alimentation déficitaire, conséquences de la basse rente et d’une forte inflation. Cette étude a apporté de nouvelles idées sur la relation entre alimentation, santé et travail dans la culture de la canne à sucre. Elle a aussi permis le développement d’une méthodologie pour une recherche plus ample dans le futur et la formation d’un matériel descriptif pour une analyse et une présentation de l’étude de cas. Des suggestions sont données, telles le changement d’habitudes alimentaires, la distribution des aliments dans les lieux de travail et la distribution de la terre, accompagnée d’une orientation technique quant à son utilisation, l’utilisation des instruments de crédit et des outils agricoles.